Clinical Pattern and Outcome of Vesicovaginal Fistulae - Tasleem Qadir (Journal of Rawalpindi Medical College, 2014)
Background: To describe the profile of patients with vesicovaginal fistula and success rate of surgery. Methods: In this cross sectional study, patients with complaints of continuous leakage of urine diagnosed on the basis of history and clinical examination as a case of vesicovaginal fistula were included. All patients with urinary incontinence due to other causes were excluded from study. Dye test was done to locate the site and assess size of fistula. For vaginal repair fistula margins were circumferentially incised and the space between vagina and bladder was dissected. The fistula repair was done in three layers and bladder was closed. Second layer was created by approximation of perivesical fascia over the first layer. In the abdominal route of repair of vesicovaginal fistula Pfannenstiel incision was preferred and extra peritoneal transvesical approach was used. Bladder was opened and ureteric openings were identified and 5 Feeding tube were passed in both ureters. Foley’s catheter was passed per urethra and a second Foley’s catheter was passed through fistula into vagina followed by inflation of balloon. Traction was applied to bring fistula closer to the operating surgeon. The bladder was dissected from the vaginal wall up to 1-2 cm around the fistula opening using Bouchery, knife and after proper mobilization repair was done without excising the margins of fistula. The vaginal fistulous opening was closed. A suprapubic catheter was placed in the bladder and the bladder was closed in two layers. Ureteric and suprapubic catheters were retained till 2-3 weeks postoperative. Elective caesarean section was advised for future pregnancy in successful cases. Patients with failed repair were counselled and referred to urology department for repeat surgery. . Results: The common cause of vesicovaginal fistula was obstructed labour ( 94.50 % ). Majority of patients (87%) were young in child bearing age between 17 to 40 years of age ,although age range was wide between 17 to 50 years. Parity of patients varied between 1-13 and only 13 ( 24.30 %) were primipara, 15(27.70%) were multipara while 26 (48 %)patients were grandmultipara. The size of fistula varied from 0.5 to 5 cm or more. surgical repair was done in 39 patients and 15 patients were referred to urology department due to ureteric or complex nature of fistula who needed interposition graft. Overall success rate was 82%.Transvaginal route of repair was used in 61.53 % in 38.47 % repair was done abdominally. Conclusion: Vesicovaginal fistula was the most common type of urogenital fistulae. The commonest cause was obstetrical trauma which was preventable by improvement of health education and maternity care in rural areas